Inguinal herniae: Valuable clues to concurrent abdominal pathology: A series of case studies describing unusual findings in ‘routine’ hernia operations which demonstrate the need for thorough surgical training - Wilson, J.M. (2011)
INTRODUCTION: The case series presented here demonstrates that the pathology encountered during inguinal hernia repair can often provide clues to concurrent pathology; the well trained surgeon's broader medical knowledge can lead to earlier diagnosis. PRESENTATION OF CASES: The case series examines four cases of men presenting with inguinal hernias, who were found to have concurrent abdominal pathology after further investigation of the intraoperative findings of the surgeon. DISCUSSION: Operating surgeons not only require the necessary surgical skills to deal with the unexpected, but must also rely on their ability to think laterally when interpreting atypical incidental findings during ‘routine’ procedures. CONCLUSION: Experience and knowledge gained through a surgeon's career is essential to enable them to correctly interpret their intraoperative findings and potentially diagnose concurrent pathology. The authors believe that surgical care practitioners, trained in just 2 years, would lack these essential skills.